Molecular Imaging of the Human Emotion Circuit - Nummenmaa Lauri; Seppälä Kerttu; Putkinen Vesa (Springer, 2025)
Emotions modulate behavioral priorities via central and peripheral nervous systems. Understanding emotions from the perspective of specific neurotransmitter systems is critical, because of the central role of affect in multiple psychopathologies and the role of specific neuroreceptor systems as corresponding drug targets. Here, we provide an integrative overview of molecular imaging studies that have targeted the human emotion circuit at the level of specific neuroreceptors and transmitters. We focus specifically on opioid, dopamine, and serotonin systems, given their key role in modulating motivation and emotions, and discuss how they contribute to both healthy and pathological emotions.
Social and Affective Neuroscience of Everyday Human Interaction